Lecturers' safety leadership and its influence towards students' safety behaviour: A case study in Politeknik Port Dickson - Zulkifly, Syazwan Syah; Shanmugam, Karthega; Azizan, Norizan (2017)
Since 2015, government has given dire attention on Technical Vocational Education and Training (TVET) as the main source of providing high-skilled human capitals to the industries. Polytechic, as one of the fully- government TVET institutes offer diploma in various engineering fields and the studies involve students with laboratories and workshops environment.Majority of polytechnic graduates get themselves employed within manufacturing, oil and gas as well as construction sector where then expose them to various hazardous working conditions. Thus, safe working behaviour is important to be instilled during their studies to prevent future injuries related to works.This study examines the influence between lecturers’ safety leadership attributes namely safety motivation, safety concern and safety policy towards students’ safety behaviour which were divided into two dimensions namely safety compliance and safety participation. A total of 345 questionnaires were distributed among the students of Politeknik Port Dickson and correlation and multiple regression analyses were performed to analyse the data. The results showed that safety motivation, safety concern and safety policy influence both dimensions of safety behaviour.Safety policy had the highest influence on safety compliance whilst safety concern had the highest influence on safety participation.